THE BENEFITS OF RUNNING AND OTHER ATHLETICS FOR HUMAN HEALTH - Radjapov U. R.; Eshpulatov J. N. (Proximus Journal Publishing, 2024)
athletics is an integral part of the physical education system. The physical education method is based on the comprehensive use of exercises that correspond to the students' functional capabilities in terms of structure, volume, and intensity. Athletic exercises are beneficial for health: they strengthen the musculoskeletal system, improve the functioning of the respiratory organs and the cardiovascular system
Keywords: athletics; physical education; academic year